(untitled) (Journal of the College of Basic Education, 2022)
The plastic arts witnessed transformations in the aesthetic manifestation through the possibilities of technical methods, by using a range of means and methods, according to the needs of art in experimentation with the aim of translating the ideas of the artist. ) New technologies such as collage, tracing, composition, assembly and other techniques,